Postnatal growth and development of Natalus mexicanus (Chiroptera: Natalidae) - Martínez-Coronel, Matías; Molina-Gutiérrez, Anubis; Hortelano-Moncada, Yolanda (THERYA, 2021)
Natalus mexicanus is a bat species distributed from northern México to Central America. It inhabits various types of tropical vegetation, roosting mainly in caves with high relative humidity and temperature, and feeding mostly on arachnids. This study investigated postnatal growth and flight development of populations under natural conditions inhabiting â€œLos Laguitosâ€ cave, Chiapas, southern México. Forty-four females and 50 males were monitored from birth to 55 days of age; at five-day intervals, we measured body mass, forearm length, cartilaginous epiphyseal gap of the fourth metacarpal-phalangeal joint, and development of four characters. We used statistical analyses and growth models to quantify the changes in morphometric parameters. Neonates are altricial; the ears began to unfold since day one, while the eyes opened at day 25. Greyish hair appeared between 25 to 35 days. Forearm length and body mass increased linearly over 35 days, then the growth rate decreased. The cartilaginous epiphyseal gap increased in size until day 25 and then started to close. The logistic equation yielded the best fit for forearm length (K = 0.07) and body mass (K = 0.10). Sustained flight was first achieved at 35 days of age. N. mexicanus neonates are altricial and relatively small compared with other bats. Eye-opening and fur development took place at a slower rate than in most species of insectivorous bats. In the Chiapas population, eye-opening, fur development, and volancy occurred more slowly relative to the population inhabiting Álamos, Sonora. These differences are probably consequences of local variations. The morphometric postnatal growth pattern of N. mexicanus was like that of other insectivorous bats, i. e., linear growth rate before the onset of flight and slowing down thereafter. As in other studies, the logistic model best fitted the growth pattern of body mass and forearm length, but growth coefficients were lower versus other tropical bats. The cartilaginous epiphyseal gap of the fourth digit closes at an intermediate age relative to other insectivorous bats. Sustained flight was attained when the relative body mass and forearm length of individuals approached adult body dimensions, as in other bat species.